2009
DOI: 10.1063/1.3257600
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of buried water molecules in phospholipid membranes by surface sum-frequency generation spectroscopy

Abstract: Polarization and experimental configuration analyses of sum frequency generation vibrational spectra, structure, and orientational motion of the air/water interface

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 30 publications
4
91
3
Order By: Relevance
“…This further shows that it is very difficult to uniquely predict Im χ (2) spectrum from the corresponding squared spectrum by recovering the missing phase information. 16,35,36 We also note that frequency dependence of Fresnel factors is not significant in the present experiment (see Figure S2). …”
mentioning
confidence: 61%
“…This further shows that it is very difficult to uniquely predict Im χ (2) spectrum from the corresponding squared spectrum by recovering the missing phase information. 16,35,36 We also note that frequency dependence of Fresnel factors is not significant in the present experiment (see Figure S2). …”
mentioning
confidence: 61%
“…If we apply these criteria, without any a priori assumptions about the nonresonant phase (see point 1), we conclude that a phase correction close to π (3.4) should be applied to the forward-corrected data [see Fig. 1(c)], rather than the value of -1.4 we concluded in our original manuscript.…”
mentioning
confidence: 99%
“…In our recent paper, we reported the counterintuitive orientation of water at charged lipid monolayer model membranes, 1 i.e., interfacial water molecules having an orientation opposite to that predicted by electrostatics. Since this type of water molecule was observed for phospholipids but not for structurally simpler surfactants, we concluded that most likely this water is localized between the lipid headgroup and its apolar alkyl chain-buried water.…”
mentioning
confidence: 99%
“…Contrary to prediction of partition in non polar phases (White 1976;Wimley and White 1996;Preston Moon and Fleming 2011) charged aminoacids such as arginine are stabilized in the bilayer, which has been explained by means of molecular dynamics in terms of water pockets (Mac Callum et al 2008;Herrera et al 2012). In this regard, it has been recognized that water may penetrate the lipid bilayer reaching the region of the carbonyl groups (Simon and McIntosh 1986;Sovago et al 2009;Disalvo and Frias 2013).…”
Section: Water In Membrane Structure and The Interfacial Propertiesmentioning
confidence: 90%